Schizophrenia-related dysbindin-1 gene is required for innate immune response and homeostasis in the developing subventricular zone - Al-Shammari, A; Bhardwaj, S; Musaelyan, K; Srivastava, L; Szele, F (Nature Publishing Group, 2018)
Schizophrenia is a neurodevelopmental disorder likely caused by environmental and genetic risk factors but functional interactions between the risk factors are unclear. We tested the hypothesis that dysbindin-1 (Dtnbp1) gene mutation combined with postnatal exposure to viral mimetic polyI:C results in schizophrenia-related behavioural changes in adulthood, and mediates polyI:C-induced inflammation in the subventricular zone (SVZ). Adult Sandy (Sdy, Dtnbp1 mutant) mice given early postnatal polyI:C injections displayed reduced prepulse inhibition of startle, reduced locomotion and deficits in novel object recognition. PolyI:C induced a canonical immune response in the SVZ; it increased mRNA expression of its toll-like receptor 3 (Tlr3) and downstream transcription factors RelA and Sp1. PolyI:C also increased SVZ Dtnbp1 mRNA expression, suggesting dysbindin-1 regulates immune responses. Dysbindin-1 loss in Sdy mice blocked the polyI:C-induced increases in mRNA expression of Tlr3, RelA and Sp1 in the SVZ. Dtnbp1 overexpression in SVZ-derived Sdy neurospheres rescued Tlr3, RelA and Sp1 mRNA expression supporting a functional interaction between dysbindin-1 and polyI:C-induced inflammation. Immunohistochemistry showed higher Iba1+ immune cell density in the SVZ of Sdy mice than in WT postnatally. PolyI:C did not alter SVZ Iba1+ cell density but increased CD45+/Iba1- cell numbers in the SVZ of Sdy mice. Finally, polyI:C injections in Sdy, but not WT mice reduced postnatal and adult SVZ proliferation. Together, we show novel functional interactions between the schizophrenia-relevant dysbindin-1 gene and the immune response to polyI:C. This work sheds light on the molecular basis for amplified abnormalities due to combined genetic predisposition and exposure to environmental schizophrenia risk factors.